Provision of Restitution and Protection Children of Victims Criminal Action - Eleanora, Fransiska Novita; Wijanarko, Dwi Seno (Technium Social Sciences Journal, 2021)
The purpose of this research is to find out how the mechanism of restitution given to children as victims of criminal acts against decency in obtaining protection for their rights as parties who suffer as a result of the actions committed by the perpetrator, in the capacity of being victims. To get restitution as a form of compensation given by the perpetrator as a result of his actions. Therefore, the child’s birthright includes not only education and health, as well as the need for food and drink or the right to an adequate environment and place to live, but also the right to fulfillment as a victim of a crime or criminal act they have experienced, which This is a form of substitution as a result of the suffering he has experienced both in terms of treatment, rehabilitation or other pain relief in terms of the psychological or psychological condition of the child as the victim. The provision of restitution is based on existing regulations and in the provisions that apart from the child who gets it can also be his family, on the basis that every child can be entitled to the fulfillment of his rights regarding being a victim of a criminal act.